2021
DOI: 10.3390/jcm10163622
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Use of Routine Clinical Parameters to Identify Patients at Risk of New-Onset Atrial Fibrillation in Acute Myocardial Infarction

Abstract: (1) Background: New-onset atrial fibrillation (NOAF) is a significant complication of acute myocardial infarction (AMI). Our study aimed to investigate whether routinely checked clinical parameters aid in NOAF identification in modernly treated AMI patients. (2) Patients and methods: Patients admitted consecutively within 2017 and 2018 to the University Clinical Centre in Gdańsk (Poland) with AMI diagnosis (necrosis evidence in a clinical setting consistent with acute myocardial ischemia) were enrolled. Medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 69 publications
3
11
0
Order By: Relevance
“…The results of Gal et al showed an association between hsTnT values measured at different intervals and newly developed AF between 24–72 h as well as 72 h after hospital admission [ 27 ]. Such data are also supported by a recent study by Raczkowska-Golanko et al [ 28 ].…”
Section: Af Predictors In Amisupporting
confidence: 86%
See 1 more Smart Citation
“…The results of Gal et al showed an association between hsTnT values measured at different intervals and newly developed AF between 24–72 h as well as 72 h after hospital admission [ 27 ]. Such data are also supported by a recent study by Raczkowska-Golanko et al [ 28 ].…”
Section: Af Predictors In Amisupporting
confidence: 86%
“…In addition, according to a study by Raczkowska-Golanko et al, left atrial diameter ≥ 41 mm and LVEF ≤ 44% were significant predictors of newly developed AF in univariate analysis in patients with AMI. EF has also been shown to be significant in multivariate analysis [ 28 ].…”
Section: Af Predictors In Amimentioning
confidence: 99%
“…This study is a sub-analysis of our previous retrospective research, where the recruitment process was precisely described [ 9 ]. The study population consisted of consecutive AMI patients hospitalized in the University Clinical Centre of Gdansk from January 2017 to December 2018.…”
Section: Methodsmentioning
confidence: 99%
“…All patients were divided into four groups: NOAF (group of patients with any newly diagnosed AF that appeared during AMI hospitalization without a prior diagnosis of AF as it was precisely described [ 9 ]); AF (group of patients with a previously documented diagnosis of AF who additionally had AF during AMI hospitalization); Prior-AF (group of patients with a previously documented diagnosis of AF who had not developed AF during AMI hospitalization); and Non-AF (group of patients with no evidence of AF during AMI hospitalization and without the prior AF diagnosis). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation